Analisis Souvenir Di Langgam Batik & Souvenir Tembung Berbahan Kain Perca Ulos - Nadya Rosa Siallagan; Misgiya Misgiya; Adek Cerah Kurni Azis (MAVIS : Jurnal Desain Komunikasi Visual, 2020)
This study aims to apply the principles of craftsmanship and variation on souvenirs made from patchwork ulos, which are carried out in the Batik & Souvenir Business on Jalan Pengapdian Gg. Musa Pulungan Dusun I Bandar setia, Tembung, North Sumatra. This research is a qualitative descriptive study. Samples for this study were 12 types of souvenirs made from ulos patchwork produced by craftsmen. The data collection methods used were observation and documentation. The results of this study showed the results of the application the principles of handicraft on 12 samples of souvenirs made from ulos patchwork produced by craftsmen.